Radioimmunotheranostic Pair Based on the Anti-HER2 Monoclonal Antibody: Influence of Chelating Agents and Radionuclides on Biological Properties - Ana Cláudia Camargo Miranda; Sofia Nascimento dos Santos; Leonardo Lima Fuscaldi; Luiza Mascarenhas Balieiro; Maria Helena Bellini; Maria Inês Calil Cury Guimarães; Elaine Bortoleti de Araújo (MDPI AG, 2021)
The oncogene HER2 is an important molecular target in oncology because it is associated with aggressive disease and the worst prognosis. The development of non-invasive imaging techniques and target therapies using monoclonal antibodies is a rapidly developing field. Thus, this work proposes the study of the radioimmunotheranostic pair, [111In]In-DTPA-trastuzumab and [177Lu]Lu-DOTA-trastuzumab, evaluating the influence of the chelating agents and radionuclides on the biological properties of the radioimmunoconjugates (RICs). The trastuzumab was immunoconjugated with the chelators DTPA and DOTA and radiolabeled with [111In]InCl3 and [177Lu]LuCl3, respectively. The stability of the RICs was evaluated in serum, and the immunoreactive and internalization fractions were determined in SK-BR-3 breast cancer cells. The in vivo pharmacokinetics and dosimetry quantification and the ex vivo biodistribution were performed in normal and SK-BR-3 tumor-bearing mice. The data showed that there was no influence of the chelating agents and radionuclides on the immunoreactive and internalization fractions of RICs. In contrast, they influenced the stability of RICs in serum, as well as the pharmacokinetics, dosimetry and biodistribution profiles. Therefore, the results showed that the nature of the chelating agent and radionuclide could influence the biological properties of the radioimmunotheranostic pair.